2020
DOI: 10.1186/s12967-019-02189-8
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microenvironment differences between primary tumor and brain metastases

Abstract: The present review aimed to discuss contemporary scientific literature involving differences between the tumor microenvironment (TME) in melanoma, lung cancer, and breast cancer in their primary site and TME in brain metastases (BM). TME plays a fundamental role in the behavior of cancer. In the process of carcinogenesis, cells such as fibroblasts, macrophages, endothelial cells, natural killer cells, and other cells can perpetuate and progress carcinogenesis via the secretion of molecules. Oxygen concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
439
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 460 publications
(470 citation statements)
references
References 106 publications
19
439
5
1
Order By: Relevance
“…Currently, accumulating evidence has suggested that the tumor microenvironment plays important roles in tumor progression and therapeutic responses (20,21). The infiltration of immune cells as well as stromal cells in the tumor microenvironment has an impact on tumor progression and prognosis (22,23). The development of cutaneous melanoma therapies, especially immunotherapy, has improved clinical outcomes (2).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, accumulating evidence has suggested that the tumor microenvironment plays important roles in tumor progression and therapeutic responses (20,21). The infiltration of immune cells as well as stromal cells in the tumor microenvironment has an impact on tumor progression and prognosis (22,23). The development of cutaneous melanoma therapies, especially immunotherapy, has improved clinical outcomes (2).…”
Section: Discussionmentioning
confidence: 99%
“…Most recently the putative role of SPMs and their precursors in the management of Covid-19 disease [ 99 ] were discussed A clinical pilot study including patients with coronary artery disease indeed demonstrated a beneficial effect of ω-3 supplementation on the lipid mediator profile: Pro-resolving mediators were restored in treated patients compared to non-treated individuals resulting in increased macrophage-driven uptake of clots. In a clinical trial focusing on patients with chronic pain a 4-week supplementation with SPM-enriched marine lipids resulted in significant reduction of pain and improved quality of life [ 100 , 101 , 102 , 103 ].…”
Section: Spms: Potential New Treatment Options For Pcosmentioning
confidence: 99%
“…Unlike other RNA viruses such as influenza, CoVs possess proofreading mechanisms, thus accumulating mutation at a slower rate [8,9]. Global sequencing efforts during the course of the COVID-19 pandemic have nevertheless identified viral variants and mutational hotspots in the SARS-CoV-2 genome [10][11][12][13][14]. Thus far, the most notable SARS-CoV-2 variant carries a D614G mutation in the spike protein and has become the most prevalent strain across geographical locations, indicating a likely fitness advantage [15].…”
Section: Introductionmentioning
confidence: 99%